DIGITAL TRANSFORMATION IN MANAGEMENT: OPPORTUNITIES AND CHALLENGES: EXPLORING HOW DIGITAL TOOLS ARE RESHAPING MANAGEMENT PRACTICES ACROSS INDUSTRIES. - Lingayat, Divya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research focuses on how digital transformation affects management practice in various industries. The paper explores the opportunities and challenges presented by digital tools like AI, data analytics, and cloud computing for managerial decision-making, operational efficiency, and organizational culture. Qualitative data analysis has been used to identify major trends, barriers, and effects of digital transformation. Findings conclude that with more digital tools, companies must have to struggle hard to put their new technology into the productive implementation, take care of increasing cybersecurity risk, and find a healthy digital culture within the organizations. Generally, the present study helps in establishing an important recommendation for using effective digital tools while providing fair support regarding transformational challenges on the employee resources and flexibility of change.